Life Stories in Context: Using the Three-Sphere Context Model To Analyze Amos's Narrative - Tuval-Mashiach, Rivka (Narrative Works, 2014)
Despite a wide theoretical consensus among narrative researchers about the importance of referring to context in analyzing narratives, it seems that the various contexts at work in individual life stories and the specific methodological implications of the importance of context are not that clear. In this paper, I will describe a model for context analysis, which refers to three distinct spheres of contexts in which narrators situate their life stories (Zilber, Tuval-Mashiach, & Lieblich, 2008). The first context involves the immediate inter-subjective relationships within and involving which a narrative is produced; the second comprises the collective social field in which a life and story have evolved; and the third surrounds the systems of broad cultural meaning or meta-narratives that underlie and give sense to any particular life story. In the second part of the paper, I will illustrate the three contexts in Amos's story, and claim that viewing his story as it is embedded through these three contexts not only situates it within a more general social framework, but also enables a deeper understanding of his identity and the core themes of his life-story.